The roles of interleukin-17A in risk stratification and prognosis of patients with sepsis-associated acute kidney injury - Heng Jin; Wei Wei; Yibo Zhao; Ai Ma; Keke Sun; Xiaoxi Lin; Qihui Liu; Songtao Shou; Yan Zhang (The Korean Society of Nephrology, 2023)
Background The aim of this study was to evaluate the roles of interleukin (IL)-17A in risk stratification and prognosis of patients with sepsis-associated acute kidney injury (SAKI). Methods We enrolled 146 sepsis patients (84 non-SAKI and 62 SAKI patients) admitted to the emergency department from November 2020 to November 2021. Patients with SAKI were differentiated based on the severity of acute kidney injury. All clinical parameters were evaluated upon admission before administering antibiotic treatment. Inflammatory cytokines were assessed using flow cytometry and the Pylon 3D automated immunoassay system (ET Healthcare). In addition, a receiver operating characteristic (ROC) curve was utilized to determine the prognostic values of IL-17A in SAKI. Results The levels of creatinine, IL-2, IL-4, IL-6, IL-17A, tumor necrosis factor alpha, C-reactive protein, and procalcitonin (PCT) were significantly higher in the SAKI group than in the non-SAKI group (p < 0.05). The level of IL-17A revealed significant differences among stages 1, 2, and 3 in SAKI patients (p < 0.05). The mean levels of PCT, IL-4, and IL-17A were significantly higher in the non-survival group than in the survival group in SAKI patients (p < 0.05). In addition, the area under the ROC curve of IL-17A was 0.811. Moreover, the IL-17A cutoff for differentiating survivors from non-survivors was 4.7 pg/mL, of which the sensitivity and specificity were 77.4% and 71.0%, respectively. Conclusion Elevated levels of IL-17A could predict that SAKI patients are significantly prone to worsening kidney injury with higher mortality. The usefulness of IL-17A in treating SAKI requires further research.